A Comparison of the Therapeutic Efficacy of Conventional and Modern Oximes Against Supralethal Doses of Highly Toxic Organophosphates in Mice - Jiří Kassa (Acta Medica, 1998)
1. The therapeutic efficacy of various oximes (pralidoxime, obidoxime, methoxime, HI-6, HLö-7, BI-6) against supralethal nerve agent poisoning (soman, sarin, cyclosin) in mice was tested. 2. New oxime BI-6, synthesized in our laboratory, is significantly more efficacious than conventional oximes but a little less efficacious than other H-oximes (HI- 6, HLö-7). 3. H-oximes (HI-6, HLö-7) seem to be the most efficacious reactivators of nerve agent-inhibited acetylcholinesterase for antidotal treatment of supralethal nerve agent poisoning in mice.